'Violence is Not Part of Our Job': A Thematic Analysis of Psychiatric Mental Health Nurses' Experiences of Patient Assaults from a New Zealand Perspective. (1st September 2014) - Baby, Maria; Glue, Paul; Carlyle, Dave
<x xml:space="preserve">Abstract</x> This paper describes psychiatric mental health nurses' (PMHN) experiences of patient assaults within mental healthcare settings using a thematic analytical approach. The aim of the study was to explore and describe psychiatric mental health nurses' experiences of patient assaults. The major findings of the study related to the nature and impact of assaults and supportive strategies associated with violence perpetrated by patients against psychiatric mental health nurses. Perpetrator risk factors for patients include mental health disorders, alcohol and drug use and the inability to deal with situational crises. The injuries sustained by nurses in the context of the study include lacerations, head injuries, dislocations and bruises. Psychological harm has also occurred, including quite severe mental health problems, such as post-traumatic stress disorder. Protective strategies for combating negative consequences of workplace violence include practice of self-defence, social support and a supportive and consultative workplace culture with access to counselling services and assistance in all aspects, including finances. The paper concludes that while healthcare employers need to provide better support services to the healthcare professionals who are assaulted, the legal system also needs to acknowledge that assaults against nurses are a violation of human rights and violence should not to be tolerated as part of working in mental healthcare settings.